The company of ants and bees (Sydney : BBC Enterprises Ltd, 1990)
Ant and Bee societies have existed for more than 25 million years - and seem to set survive long after we have disappeared. What is the secret of their longevity? Why are they so much more cooperative than us, and don't quarrel among themselves. There are lessons that we can learn by studying the way these insect societies are organised
Keywords: Hymenoptera -- Behavior; Ants -- Behavior; Bees -- Behavior; Social behavior in animals